2023
DOI: 10.1371/journal.pone.0285425
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal content and microbial characteristics of soil plant system in Dabaoshan mining area, Guangdong Province

Abstract: The disordered mining of Dabaoshan lead-zinc mineral resources in Shaoguan has brought serious harm to the regional ecological environment. In order to investigate the heavy metal pollution status and microbial characteristics of soil plant system in mining area, The distribution of heavy metals in the soil, the activity of soil microorganisms and the accumulation characteristics of heavy metals in the dominant plant Miscanthus floridulus were studied. The results indicated that metal element contents of Misca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Combined with previous research results, the unprocessed metallurgical wastewater of Dabaoshan multimetal mine in northern Guangdong Province was directly discharged into Hengshi River, causing serious harm to the environment along the the Hengshi River Basin [52]. The acid and polluted wastewater discharged by Dexing Copper Mine in Jiangxi Province contaminated the Le'an River and caused harm to animals, plants, and farmland along the riverbanks [53]. The results of previous research have shown that acidic wastewater generated by mining activities and its illegal discharge are another important cause of Cd pollution in the Wenyu Stream [54].…”
Section: Acid Mine Drainage Source Of Cadmium In the Wenyu Streammentioning
confidence: 67%
“…Combined with previous research results, the unprocessed metallurgical wastewater of Dabaoshan multimetal mine in northern Guangdong Province was directly discharged into Hengshi River, causing serious harm to the environment along the the Hengshi River Basin [52]. The acid and polluted wastewater discharged by Dexing Copper Mine in Jiangxi Province contaminated the Le'an River and caused harm to animals, plants, and farmland along the riverbanks [53]. The results of previous research have shown that acidic wastewater generated by mining activities and its illegal discharge are another important cause of Cd pollution in the Wenyu Stream [54].…”
Section: Acid Mine Drainage Source Of Cadmium In the Wenyu Streammentioning
confidence: 67%